KUALITAS NUTRISI SILASE JERAMI PADI YANG DISUPLEMENTASI DAUN TURI (Sesbania grandiflora) - Kaban,, M.J.F.,; Cakra,, I G. L. O.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2025)
Rice straw is characterized by high crude fiber content and low crude protein, making it afeed ingredient with limited nutritional value. This condition requires increasing its nutritionalvalue through the addition of protein-rich supplements. The study aimed to examine the effect of Sesbania grandiflora leaf meal as a supplement on the nutritional composition of rice strawsilage. A completely randomized design (CRD) with four treatments and four replications wasused in this study, resulting in a total of 16 experimental units. The study was conducted at thePlant and Feed Laboratory, Bukit Campus, Faculty of Animal Husbandry, Udayana University.The treatments used included: P1 = 85% rice straw + 10% pigeon pea leaf meal + 5% molasses,P2 = 75% rice straw + 20% pigeon pea leaf meal + 5% molasses, P3 = 65% rice straw + 30%pigeon pea leaf meal + 5% molasses, P4 = 55% rice straw + 40% pigeon pea leaf meal + 5%molasses. Statistical analysis showed that supplementation with turi leaf meal significantlyreduced dry matter and crude fiber content while increasing organic matter and crude proteincontent in rice straw silage. Meanwhile, silage pH did not change significantly betweentreatments. Treatment P4 (40% turi leaf meal) provided the best results, with the highest crudeprotein and organic matter content, and the lowest crude fiber content compared to the othertreatments. These results indicate that the use of turi leaf meal or Sesbania grandiflora up to 40%is the optimal level for increasing the nutritional value of rice straw silage. ABSTRAK Jerami padi dicirikan oleh kandungan serat kasar yang tinggi serta protein kasar yangrendah, sehingga menjadikannya sebagai bahan pakan dengan nilai nutrisi terbatas. Kondisi inimemerlukan peningkatan nilai gizinya melalui penambahan suplemen kaya protein. Penelitianbertujuan untuk mengkaji pengaruh tepung daun Sesbania grandiflora sebagai suplementerhadap komposisi nutrisi silase jerami padi. Rancangan acak lengkap (RAL) dengan empatperlakuan dan empat ulangan digunakan dalam penelitian ini sehingga total terdapat 16 satuanpercobaan. Penelitian dilaksanakan di Laboratorium Tumbuhan dan Pakan Kampus BukitFakultas Peternakan Universitas Udayana. Perlakuan yang digunakan meliputi: P1 = 85%jerami padi + 10% tepung daun turi + 5% molase, P2 = 75% jerami padi + 20% tepung daunturi + 5% molase, P3 = 65% jerami padi + 30% tepung daun turi + 5% molase, P4 = 55% jeramipadi + 40% tepung daun turi + 5% molase. Analisis statistik menunjukkan bahwa suplementasitepung daun turi secara signifikan dalam menurunkan kadar bahan kering dan serat kasarsekaligus meningkatkan kadar bahan organik dan protein kasar dalam silase jerami padi.Sementara itu, pH silase tidak berubah secara signifikan antar perlakuan. Perlakuan P4 (40%tepung daun turi) memberikan hasil terbaik, dengan kadar protein kasar dan bahan organiktertinggi, serta kadar serat kasar terendah dibandingkan dengan perlakuan lainnya. Hasil inimemperlihatkan bahwa penggunaan tepung daun turi atau sesbania grandiflora hingga 40%merupakan level optimal untuk meningkatkan nilai nutrisi silase jerami padi.